Cyber Public Relations Strategy of PT Kilat Dotcom Indonesia in Enhancing Corporate Image Through Social Media Instagram in 2024 - Rachel Pytaloka Damayanti; Aswad Ishak (Jogjakarta Communication Conference (JCC), 2025)
In the rapidly evolving digital era, media companies are required to manage their positive image through effective communication strategies. PT. Kilat Dotcom Indonesia (Kilat.com), as a digital media company, faces challenges in increasing engagement and maintaining a positive image amidst intense industry competition. This study aims to analyze the Cyber Public Relations (Cyber PR) strategy implemented by PT Kilat Dotcom Indonesia (Kilat.com) to enhance corporate image through social media, particularly Instagram, in 2024. The research employs a qualitative descriptive method using in-depth interviews and documentation. The findings indicate that PT Kilat Dotcom Indonesia applies Cyber PR strategies based on Philips & Young’s (2009) framework, which includes four key elements: transparency, internet porosity, the internet as an agent, and richness in content and reach. These strategies enable the company to increase user engagement, build public trust, and strengthen its image as an informative and credible digital news provider. With these findings, PT Kilat Dotcom Indonesia can shape public perception of digital media companies and maintain its competitiveness in the digital media industry.